Analysis of Light in Office Space Based on Topic 4 of National Building Regulations in Different Climates (Case Study: Iran) - P. Ildarabadi; A. Ghalehnovi (Iranica Journal of Energy and Environment)
Daylight studies on office buildings are very important due to the use of artificial lighting and their energy consumption during daytime hours and also providing visual comfort in working spaces. In compliance with the National Building Code of Iran, it is mandated that office spaces possess access to natural light and ventilation through one or more windows, constituting at least 12.5% of the total glass area in relation to the floor space. This research is devoted to the investigation and assessment of the appropriateness of this ratio in diverse climates across Iran. For this purpose, the index of Daylight Autonomy (DA), Useful Daylight Illuminance (UDI) and also Annual Sunlight Exposure (ASE) metrics were used on an office space in 5 cities of Isfahan, Mashhad, Chabahar, Tabriz and Ahvaz, in Grasshopper software and Honeybee and Ladybug plug-ins. The analysis underscores a robust, direct correlation between the ratio of glass surface area to floor space and the levels of natural illumination. Notably, the intensity of light radiation, as indicated by DA, is most favorable in Isfahan and Mashhad, and least favorable in Ahvaz. Furthermore, UDI values exhibit a proportional relationship with light behavior in the environments of Isfahan and Ahvaz, respectively. Chabahar city emerges with the most favorable ASE values. The findings underscore that the current prescribed standard may not be across the country applicable or optimal across all climates. It is advised to make climate-specific adaptations to this standard, providing designers with increased assurance in its use throughout the design process.